2017
DOI: 10.3390/rs9050503
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Error in IMERG Precipitation Estimates under Different Topographic Conditions and Temporal Scales over Mexico

Abstract: This study evaluates the precipitation product of the Integrated Multi-satellitE Retrievals for Global Precipitation Measurement (IMERG) over the Mexican region during the period between April 2014 and October 2015 using three different time scales for cumulative precipitation (hourly, daily and seasonal). Also, the IMERG data have been analyzed as a function of elevation given the rain gauges from the automatic meteorological stations network, located within the area of study, which are used as a reference. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
34
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 21 publications
4
34
0
1
Order By: Relevance
“…4). This behaviour confirms longer time averages are more representative, as also seen by Caracciolo et al (2018), Mayor et al (2017), , Tang et al (2016a), among others. Overall, the CC presented values higher than 0.80 for 90% of the cells available for the Brazilian territory in the monthly analysis, most of them concentrated close to the mean (CC = 0.92) (Fig.…”
Section: Grid-scale Evaluationsupporting
confidence: 87%
See 1 more Smart Citation
“…4). This behaviour confirms longer time averages are more representative, as also seen by Caracciolo et al (2018), Mayor et al (2017), , Tang et al (2016a), among others. Overall, the CC presented values higher than 0.80 for 90% of the cells available for the Brazilian territory in the monthly analysis, most of them concentrated close to the mean (CC = 0.92) (Fig.…”
Section: Grid-scale Evaluationsupporting
confidence: 87%
“…However, the performance of the GPM products needs to be critically evaluated in different regions of the world as sources of information for both end users and data producers (Prakash et al, 2018). Several recent studies evaluated different IMERG products in complex areas under distinct climatic and geographic aspects worldwide by using ground-based data and/or comparisons with other satellite products such as TMPA (Anjum et al, 2018;Asong et al, 2017;Beria et al, 2017;Dezfuli et al, 2017;Gebregiorgis et al, 2018;Lelis et al, 2018;Mahmoud et al, 2018;Mayor et al, 2017;Mitra et al, 2018;Muhammad et al, 2018;O and Kirstetter, 2018;Oliveira et al, 2018;Prakash et al, 2018Prakash et al, , 2016Satgé et al, 2017;Sungmin et al, 2017;Tan and Duan, 2017;Tan and Santo, 2018;Tang et al, 2016aTang et al, , 2016bWang et al, 2017;Zhang et al, 2018). Most of the aforementioned studies showed good agreement of the IMERG products with the gauge, radar, and TMPA data.…”
mentioning
confidence: 99%
“…Tang, Ma, et al (2016) evaluated a 3-month IMERG V03 data set and found a slight but nonsignificant improvement in the diurnal cycle of precipitation amount. Mayor et al (2017) concluded that IMERG performed fairly well but still had a 2-hr lag in the peak time in the countrywide mean diurnal cycle over Mexico. By using six gauge stations in Africa, Dezfuli et al (2017) also proved the improved performance of IMERG in terms of diurnal cycle.…”
Section: Introductionmentioning
confidence: 99%
“…As the spatiotemporal resolution and coverage of GPM have been extended beyond the TRMM resolution and coverage, the performance of the GPM IMERG products needs to be evaluated and validated globally.Several studies have compared the GPM IMERG and TRMM products with ground-based measurements, i.e., rain gauge and weather radar [4,6,10,[15][16][17][18][19], considering their hydrological applications [14,[20][21][22]. Also, different GPM IMERG products regarding temporal resolutions have been evaluated considering various climatic and topographic conditions using various statistical measures across the world [5,[23][24][25][26][27][28][29][30]. Although most of these studies confirmed the improvement of the IMERG products relative to those of the TRMM Multi-satellite Precipitation Analysis (TMPA), a more comprehensive investigation is still essential to better understand the IMERG performance in various regions of the world taking into consideration different products' versions and temporal resolution.…”
mentioning
confidence: 99%